The Renin–Angiotensin System Modulates SARS-CoV-2 Entry via ACE2 Receptor - Sophia Gagliardi; Tristan Hotchkin; Hasset Tibebe; Grace Hillmer; Dacia Marquez; Coco Izumi; Jason Chang; Alexander Diggs; Jiro Ezaki; Yuichiro J. Suzuki; Taisuke Izumi (Viruses)
The renin–angiotensin system (RAS) plays a central role in cardiovascular regulation and has gained prominence in the pathogenesis of Coronavirus Disease 2019 (COVID-19) due to the critical function of angiotensin-converting enzyme 2 (ACE2) as the entry receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Angiotensin IV, but not angiotensin II, has recently been reported to enhance the binding between the viral spike protein and ACE2. To investigate the virological significance of this effect, we developed a single-round infection assay using SARS-CoV-2 viral-like particles expressing the spike protein. Our results demonstrate that while angiotensin II does not affect viral infectivity across concentrations ranging from 40 nM to 400 nM, angiotensin IV enhances viral entry at a low concentration but exhibits dose-dependent inhibition at higher concentrations. These findings highlight the unique dual role of angiotensin IV in modulating SARS-CoV-2 entry. In silico molecular docking simulations indicate that angiotensin IV was predicted to associate with the S1 domain near the receptor-binding domain in the open spike conformation. Given that reported plasma concentrations of angiotensin IV range widely from 17 pM to 81 nM, these levels may be sufficient to promote, rather than inhibit, SARS-CoV-2 infection. This study identifies a novel link between RAS-derived peptides and SARS-CoV-2 infectivity, offering new insights into COVID-19 pathophysiology and informing potential therapeutic strategies.